Using omics approaches to dissect the therapeutic effects of Chinese herbal medicines on gastrointestinal cancers - Li, Si-Yi; Wang, Wei-Jia; Li, Qiu-Yue; Yang, Peng-Hui; Li, Xin-Long; Yan, Yan; Yuan, Yong; Feng, Yi-Bin; Hong, Ming (Frontiers in Pharmacology, 2022)
Chinese herbal medicines are a rich source of potential leads for anti-cancer drugs development. However, there are various differences between the pharmacology of Chinese herbal medicines and modern synthetic chemicals, which significantly obstruct the development of herbal-derived drugs. For addressing this challenge, novel approaches associated with transcriptomics, proteomics, genomics, and metabolomics have been applied to dissect the pharmacological mechanisms of Chinese herbal medicines in cancer treatment. In recent years, numerous of Chinese herbal medicines have shown potential antitumor effects and eliminating the side effects of conventional tumor treatment on different types of gastrointestinal (GI) cancers. The current study provides an overview of the recent research in dissecting Chinese herbal medicines by omics approaches in gastrointestinal cancers, and illustrates the potential of omics methods in herbal-derived drugs discovery. With the development of novel technologies, the number of fields in omics and their applications in GI cancers treatment are quickly increasing. OMICS methods can efficiently reveal the key molecular targets and intracellular interaction networks of Chinese herbal medicines in GI cancers treatment. Thus, this study summarizes the application of different OMICS based approaches in illustrating the underlying mechanisms of using Chinese herbal medicines in treating GI cancers and eliminating the side effects of conventional GI cancer treatment though examining therapeutic targets and signaling pathways. We also provide directions for future research in this filed.